2016
DOI: 10.7732/kjpr.2016.29.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cells Activity, Nitrite Scanvenging and ABTS Radical Scavenging Activities of Codonopsis lanceolata Ethanol Extracts from Districts in Korea

Abstract: This study was executed to evaluate the immune activity, nitrite scavenging activity and ABTS radical scavenging activity against extracts of various concentration of ethanol solvent from Codonopsis lanceolata cultured at 6 local regions. The immune responses from both human T and B cell line was significantly enhanced in the cell growth compared to control while the cell growth was influenced at a certain period of culture. The results revealed that the cell growth of both human T and B cell was altered in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In another study, antioxidant potential of M. charantia samples obtained from different regions was determined by using DPPH, ABTS and Nitrite scavenging tests. As a result of the study, it was reported that the plant sample had significant antioxidant activity [25]. In a study conducted in Turkey, it was reported that the plant has a significant antioxidant effect on rats [26].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In another study, antioxidant potential of M. charantia samples obtained from different regions was determined by using DPPH, ABTS and Nitrite scavenging tests. As a result of the study, it was reported that the plant sample had significant antioxidant activity [25]. In a study conducted in Turkey, it was reported that the plant has a significant antioxidant effect on rats [26].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The species is known to exert various pharmacological effects in humans. The roots of C. lanceolata mainly contain triterpenoid saponins, including codonolasides I-V and lancemaside A-G (Boo et al, 2016;Moon et al, 2018). The saponins exhibit anti-inflammatory effects for conditions such as bronchitis and cough, insomnia, and hypomnesia.…”
Section: Introductionmentioning
confidence: 99%